2018
DOI: 10.1002/jcop.22151
|View full text |Cite
|
Sign up to set email alerts
|

Informal caregiving experiences in posttraumatic stress disorder: A content analysis of an online community

Abstract: This study explored the experiences of individuals who self‐identify as providing support to a friend, family member, or significant other with posttraumatic stress disorder (PTSD). We analyzed and coded a total of 345 posts from an online support forum, with reference to 13 categories (finances, life interference, venting/emotional expression, maltreatment, sexual behavior, distress, prevented expression, physical health, communication, no personal space, isolation, and compassion fatigue). Categories for cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Studies, however, have documented physical and mental consequences of caregiver burden, including depression, anxiety, social isolation, loneliness, difficulty balancing professional and personal responsibilities, increased occurrence of chronic conditions (Aoun et al, 2018; Brodaty & Donkin, 2009; Deist & Greeff, 2017), difficulty accessing support resources, compassion fatigue (Ferrell et al, 2019), and suicidal ideation (dos Santos Treichel et al, 2018), underlining the importance of developing resilience in the context of caregivers themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Studies, however, have documented physical and mental consequences of caregiver burden, including depression, anxiety, social isolation, loneliness, difficulty balancing professional and personal responsibilities, increased occurrence of chronic conditions (Aoun et al, 2018; Brodaty & Donkin, 2009; Deist & Greeff, 2017), difficulty accessing support resources, compassion fatigue (Ferrell et al, 2019), and suicidal ideation (dos Santos Treichel et al, 2018), underlining the importance of developing resilience in the context of caregivers themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Online communities have previously been described as a valuable resource for understanding the experiences of individuals affected by trauma (Ferrell, Russin, & Hardy, 2019; Russin & Ferrell, 2019). One public resource that is utilized as an outlet for emotional expression, peer support, and queries among individuals with PTSD is an online discussion forum entitled MyPTSD.…”
Section: Introductionmentioning
confidence: 99%
“…In one case, Dolce (2011) showed that a user shared his/her experience on how via feedback from community members he/she noticed that their doctor is not experienced enough to manage the illness resulting in changing the doctor, ‘ Changing doctors was the result and probably a life‐saving decision’ . Our analysis shows that OHCs enable caregivers and other users to express and reveal their challenges and emotionally sensitive issues not generally revealed to others in a completely anonymous manner (Ferrell et al., 2019). Hence, by unfolding and expressing the bottled‐up emotions, needs and personal information, caregivers create an opportunity for themselves and also other users to access and share valuable support.…”
Section: Resultsmentioning
confidence: 90%
“…Despite, informal caregivers improving the resilience of older adults, they also experience substantial challenges, such as emotional turmoil, challenges to interpersonal relationships and barriers to care (Ferrell et al., 2019), which can negatively impact all dimensions of daily life and the resilience of both informal caregivers and older adults. Informal caregivers who dedicate 20 hr or more per week to care‐giving affairs are negatively impacted financially as they have to reduce their working hours significantly or even leave their job.…”
Section: Introductionmentioning
confidence: 99%